Synthesis of bioactive glass using cellulose nano fibre template - Sh, M. Sarmast; George, S.; Awang Biak, Dayang Radiah; Hoey, D.; Abdullah, N.; Kamarudin, S. (Elsevier, 2022)
This study introduces a templating approach using a cellulosic suspension to create a porous SiO2–CaO–P2O5–Na2O bioactive glass material. Sol-gel approach was used as the synthesis method. Carbon nanofibers in suspension form was used as the templating material. The amount of CNF used in the experiment ranged from 5% to 25% by volume. The morphology, porosity, crystallinity of the combeite phase, mechanical and chemical properties of the BG samples were examined. The findings show that the templating method had no effect on the formation of the required functional elements, such as Si, Ca, Na and P. The porosity of the BG materials improves by 15% after templating compared to the neat sample. The formed pores were assumed to be homogenous based on the uniform adsorption and desorption BET profiles. The crystallization mechanisms during the sintering process were affected by the templating approach, indicating the need for a specific amount of template to be used in the preparation step. Both the sintering temperatures and the CNF content affected the formation of the combeite phase. The BG samples had excellent mechanical properties and are suitable for use in cancellous bone applications. As a result, this study shows a novel method for synthesizing porous bioactive glass materials via the sol-gel method and a CNF suspension as a template.